Characterization of the molecular chaperone ClpB from the pathogenic spirochaete Leptospira interrogans - Krajewska, Joanna (PLoS One, 2017)
Leptospira interrogans is a spirochaete responsible for leptospirosis in mammals. The molecular mechanisms of the Leptospira virulence remain mostly unknown. Recently, it has been demonstrated that an AAA(+) chaperone ClpB (a member of the Hsp100 family) from L. interrogans (ClpB(Li)) is not only essential for survival of Leptospira under the thermal and oxidative stresses, but also during infection of a host. The aim of this study was to provide further insight into the role of ClpB in the pathogenic spirochaetes and explore its biochemical properties. We found that a non-hydrolysable ATP analogue, ATPγS, but not AMP-PNP induces the formation of ClpB(Li) hexamers and stabilizes the associated form of the chaperone. ADP also induces structural changes in ClpB(Li) and promotes its self-assembly, but does not produce full association into the hexamers. We also demonstrated that ClpB(Li) exhibits a weak ATPase activity that is stimulated by κ-casein and poly-lysine, and may mediate protein disaggregation independently from the DnaK chaperone system. Unexpectedly, the presence of E. coli DnaK/DnaJ/GrpE did not significantly affect the disaggregation activity of ClpB(Li) and ClpB(Li) did not substitute for the ClpB(Ec) function in the clpB-null E. coli strain. This result underscores the species-specificity of the ClpB cooperation with the co-chaperones and is most likely due to a loss of interactions between the ClpB(Li) middle domain and the E. coli DnaK. We also found that ClpB(Li) interacts more efficiently with the aggregated G6PDH in the presence of ATPγS rather than ATP. Our results indicate that ClpB’s importance during infection might be due to its role as a molecular chaperone involved in reactivation of protein aggregates.